Combined Diagnostic Efficacy of Neutrophil-to-Lymphocyte Ratio (NLR), Platelet-to-Lymphocyte Ratio (PLR), and Mean Platelet Volume (MPV) as Biomarkers of Systemic Inflammation in the Diagnosis of Colorectal Cancer - Krivokapic, Zoran; Dumic, Igor; Lalic, Daria; Radoman Vujacic, Irena; Dimitrijevic, Ivan; Stojkovic, Mirjana; Stankovic, Sanja; Pavlovic Markovic, Aleksandra; Stojkovic Lalosevic, Milica; Milovanovic, Tamara (Disease markers, 2019)
Background. Systemic inflammation in colorectal cancer (CRC) may be reflected by neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), and mean platelet volume (MPV). This study was designed to investigate the efficiency of preoperative NLR, PLR, and MVP as a tool for the assessment of tumor characteristics in newly diagnosed patients with CRC. Patients and Methods. For 300 patients and 300 healthy volunteers, complete blood counts with automated differential counts were performed. The NLR was calculated by dividing the absolute neutrophil count by the absolute lymphocyte count; PLR was calculated by dividing the absolute platelet count by the absolute lymphocyte count. The diagnostic performance of NLR, PLR, and MVP was estimated by ROC curve. Results. ROC curve analysis showed high diagnostic efficacy of NLR and PLR in CRC patients with cut-off values of 2.15 (AUC=0.790, 95% CI 0.736-0.884, Se=74.1%, and Sp=73%) and 123 (AUC=0.846, 95% CI 0.801-0.891, Se=73.5%, and Sp=80%) compared to healthy controls, respectively. The diagnostic efficacy of three combined markers was superior compared with individual markers (AUC=0.904, 95% CI 0.812-0.989, Se=96%, and Sp=70%). Conclusion. NRL, PLR, and MPV may be useful markers in diagnostic and early recognition of different stages of CRC; additionally combined all together have stronger diagnostic efficacy.